An experimental study of hull girder loads on an intact and damaged naval ship. (15th March 2017) - Begovic, E.; Day, A.H.; Incecik, A.
Abstract: The study reported in this paper is focused on experimental investigation of the hull girder loads on an intact and damaged naval ship DTMB 5415 at zero speed. The experimental campaign was carried out in head and beam regular waves at the University of Strathclyde. The effect of the use of moorings in the model experimental setup was investigated in the context of loads assessment, and the moorings are shown to influence the measured hull girder loads at some wave frequencies compared to the free drift case. Therefore the tests in beam seas are performed with free drifting model while the moored model setup was adopted for head seas. The results for ship motions are compared with those from a previous campaign giving an insight into repeatability and uncertainty of measurements. The roll decay of the ship in both intact and damaged conditions is analysed and the linear and quadratic extinction coefficients for the model and the ship scale are reported and detailed discussion on intact-versus-damaged ship roll damping behaviour is given. The results for the hull girder loads are presented for intact and damaged ship. An investigation of the nonlinear effects due to wave height variation in the range wave height to wave length from 1/50 to 1/22 on the shear force and bending moment values was carried out for a range of wave lengths to ship length ratios from 0.8 to 1.4. The results of the extensive campaign are compared against similar experimental studies forming a benchmark data for validation of numerical methods. Highlights: Motions and loads of intact and damaged stationary DTMB model 5415 were measured. Motions and loads results are presented in form of RAO and compared with previous campaigns. The comparison of the measured loads of the intact against the damages ship is given. Roll damping for intact and damaged model is measured, analysed and commented. Nonlinearity due to the wave amplitude variation has been investigated for loads.